2020
DOI: 10.1021/acs.macromol.0c01400
|View full text |Cite
|
Sign up to set email alerts
|

Programming Self-Assembly and Stimuli-Triggered Response of Hydrophilic Telechelic Polymers with Sequence-Encoded Hydrophobic Initiators

Abstract: A recent communication from our laboratory demonstrated that the presence of a small hydrophobic initiator residue (core) in water-soluble telechelic dibromo homopolymers can drive their self-assembly in aqueous solution into micelle-like nano-objects in which polymer chains adopt a folded conformation. Centered on the use of site-selective cleavable difunctional initiators, we demonstrate herein that this approach offers bottom-up and facile access to multistimuli-sensitive nanostructures for effective cargo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…, pyridinium p -toluenesulfonate) as a catalyst under mild reaction conditions ( e.g. , room temperature). However, we decided to avoid acid catalysis to simplify our approach and avoid possible acid traces remaining after the synthesis that could catalyze the degradation of acetals, severely affecting the stability of the covalent cross-linking network. In addition, the thermal “click” addition of hydroxyl groups with divinyl ethers has previously been studied with small-molecule compounds, showing excellent yields (>95%) and also proving that the dynamic exchange mechanism is a combination of acetal metathesis and transacetalization. , The selection of SKL as a starting material was rationalized based on the inherent rigidity and presence of multiple aliphatic and phenolic hydroxyl groups, which are expected to provide enough cross-linking sites for the formation of dynamic covalent networks .…”
Section: Resultsmentioning
confidence: 99%
“…, pyridinium p -toluenesulfonate) as a catalyst under mild reaction conditions ( e.g. , room temperature). However, we decided to avoid acid catalysis to simplify our approach and avoid possible acid traces remaining after the synthesis that could catalyze the degradation of acetals, severely affecting the stability of the covalent cross-linking network. In addition, the thermal “click” addition of hydroxyl groups with divinyl ethers has previously been studied with small-molecule compounds, showing excellent yields (>95%) and also proving that the dynamic exchange mechanism is a combination of acetal metathesis and transacetalization. , The selection of SKL as a starting material was rationalized based on the inherent rigidity and presence of multiple aliphatic and phenolic hydroxyl groups, which are expected to provide enough cross-linking sites for the formation of dynamic covalent networks .…”
Section: Resultsmentioning
confidence: 99%
“…The use of hydrophobic DIs containing cleavable functions enables the reduction of the number-average molar mass (M n ) by half after degradation, which dramatically modifies the amphiphilic balance (Scheme 1C), 41,42 further resulting in the breakdown of the nanoassemblies. 39,40 Herein, we report a facile strategy to prepare dual pH and reduction-breakable micelle-like nanoassemblies, formed from the self-directed assembly of fully hydrophilic poly(triethylene glycol monomethyl ether acrylate)s [poly(TEGA)s] prepared via SET-LRP employing a hydrophobic DI integrating acetal and disulfide cleavable linkages as double dual "keystone" units. Although dual acidic pH/reduction-responsive degradable block copolymer systems have received increasing attention for cellular delivery applications by means of increased acidity and glutathione (thiol) concentration of tumor cells or tissues compared to the healthy ones, 35,43−45 this is the first example of homopolymers that act in the same way as amphiphilic block copolymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previously, we have shown that fully hydrophilic telechelic dibromopolymers prepared by combining single-electron transfer living radical polymerization (SET-LRP) with hydrophobic difunctional initiators (DIs) are a convenient means of synthesizing associative telechelic homo or random polymers with predicted molecular weight, narrow polydispersity, and high chain-end functionality (Scheme C). , The aqueous self-assembly of these amphiphilic homopolymers results in initiator residue incorporation at the hydrophobic core of micelle-like nanoassemblies via chain folding. This amphiphilic homopolymer design is especially attractive in terms of control over the disassembly process because the chemical engineering of DI enables the programming of a predetermined degradation code by introducing labile linkages into its design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important developments in this field are organocatalyzed ATRP 32,33 and photoinduced electron transfer reversible addition‐fragmentation chain‐transfer (PET‐RAFT) polymerization 34 . Recently, sequence encoded hydrophobic initiators have been employed to tailor the self‐assembly and stimuli‐responsiveness of hydrophilic telechelics 35 . Herein, we describe a new design of symmetric linear pentablock copolymers by employing a bifunctional perfluoroalkyl PF‐initiator for atom transfer radical polymerization (ATRP) to synthesize triphilic PPO‐ b ‐PGMA‐ b ‐PF‐ b ‐PGMA‐ b ‐PPO pentablock copolymers by a combined ATRP and Cu(I) catalyzed azide‐alkyne cycloaddition (CuAAC) approach.…”
Section: Introductionmentioning
confidence: 99%